EVALUATION OF ZONATION OF THE MANGROVE CONSERVATION AREAS IN PAMURBAYA - Viv Djanat Prasita; Agus Subianto; Asbar Asbar (UPT Penerbitan Universitas Jember, 2016)
This study was conducted to evaluate the zonation of MCA in Pamurbaya. The methods are field survey, GIS methods using satellite imagery in 2012, 2014, and 2015. The results showed that the zoning of MCA has no less effective. It can be seen from the conditions, ie.: the buffer zones have been partly used for settlements (+ 13.35 Ha) and the core zone has been used for ponds (+ 462.30 Ha). The areas of ponds in the core zone were reduced by 18.39 ha in 2012 to 2014 but increased by 4.09 ha in 2014 to 2015.